Generation of a colony of homozygous K18-hACE2 transgenic mice for the evaluation of vaccine and therapeutic candidates against SARS-CoV-2 (FAVE Sección Ciencias Veterinarias, 2022)
SARS-CoV-2 is the causative etiological agent of the COVID-19 disease that started a pandemic in late 2019. Among different animal models for this disease, the K8-hACE2 transgenic mouse model, originally developed for the study of SARS-CoV-1, proved to be of great relevance in the current context. Considering that those mice are marketed as hemizygous and given that homozygous mice for the K18-hACE2 transgene are not commercially available, this work aimed to describe the creation of a colony of homozygous K18-hACE2-Tg/Tg mice under controlled environmental conditions. For the F1 progeny 10 hemizygous mice (7 females and 3 males), between 6-8 weeks of age, from The Jackson Laboratory (USA) were used. From the F1, 78 animals were identified by PCR genotyping: 62 hemizygous (Tg/0) and 16 wild types (0/0). Those animals identified as transgenic were crossed with C57BL/6J mice to select the homozygous parents that generated 100% hemizygous in F2. From a total of 224 analyzed offspring, 7 homozygous K18-hACE2-Tg/Tg parents were obtained, which were used for the foundation colony of homozygous K18-hACE2-Tg/Tg mice. The homozygous K18-hACE2-Tg/Tg mouse colony developed in this work will be able to use for the study of pathogenesis and the evaluation of possible therapeutics against SARS-CoV-2.
Keywords: K18-hACE2; genotyping; preclinical model; COVID-19